2017
DOI: 10.1111/trf.14064
|View full text |Cite
|
Sign up to set email alerts
|

A novel B allele with c.28 + 5885C>T substitution in the erythroid cell–specific regulatory element identified in an individual with phenotype B3

Abstract: The ABO blood group system is the most clinically important in blood transfusion. The decreased expression levels of A or B antigens of the ABO subtype often present difficulties in blood typing and cross-matching for clinical transfusion. B 3 is the most common B subtype, which has a frequency of approximately 1 in 900 in the Chinese population. The underlying mechanisms of the B 3 phenotype were diversified. Several mutations in the exons, splicing site, and mutations in the promoter have been reported for B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…) . Similarly, single‐nucleotide substitution of c.28 + 5885C > T was reported around the RUNX1 motif in an individual with B 3 . These genetic studies confirmed the regulatory significance of the +5.8‐kb site for erythroid cell–specific expression of ABO in vivo.…”
Section: Regulatory Regions For Abo Expressionsupporting
confidence: 64%
“…) . Similarly, single‐nucleotide substitution of c.28 + 5885C > T was reported around the RUNX1 motif in an individual with B 3 . These genetic studies confirmed the regulatory significance of the +5.8‐kb site for erythroid cell–specific expression of ABO in vivo.…”
Section: Regulatory Regions For Abo Expressionsupporting
confidence: 64%
“…The erythroid cell‐specific regulatory activity of the +5.8‐kb site was found to be dependent on the binding of the haematopoietic transcription factors GATA and runt‐related transcription factor 1 (RUNX1), and variants in the binding motifs of these factors were shown to reduce the transcriptional activity of the +5.8‐kb site [4, 7]. To date, seven variants in the +5.8‐kb site have been reported to cause weak B phenotypes, most of which have been identified in Chinese and Japanese individuals [4, 5, 8, 10, 11, 13]. In the Japanese population, B m is the most common B subgroup, the main mechanism of which is the 5.8‐kb deletion (g.10157_15927del) [4, 8, 19].…”
Section: Discussionmentioning
confidence: 99%
“…In the Japanese population, B m is the most common B subgroup, the main mechanism of which is the 5.8‐kb deletion (g.10157_15927del) [4, 8, 19]. In contrast, in the Chinese and Korean populations, B 3 is the most common B subgroup [10, 14], and the 5.8‐kb deletion has not been reported. In this study, which included 16 Koreans with weak B phenotypes, the most frequent variant was g.10925C>T located in the RUNX1 motif of the +5.8‐kb site (Figure 1b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The full coding regions of the ABO gene, the upstream CBF/NF-Y enhancer region, promoter, and the erythroid cell-specific regulatory elements in intron 1 were nucleotide sequenced as previously published. 5 Exons 6 and 7 of the ABO gene and the intervening intron were cloned and the two haplotypes sequenced (TOPO TA cloning kit; Life Technologies, Carlsbad, CA).…”
Section: Brief Methodsmentioning
confidence: 99%